Relationships among nursing students’ self-concept clarity, meaning in life, emotion regulation ability and depression: Testing a moderated mediation model - Hong, Youjuan; Zhang, Xuan; Wu, Weiwei; Chen, Jingjing; Lin, Yan; Zhao, Junyu; Xiao, Huimin (Frontiers in Psychology, 2022)
Although self-concept clarity has been shown to be an important factor of depression, little is known about the inner mechanisms underlying this relationship. The study is to examine the potential mediating role of meaning in life and the moderation of emotion regulation ability in the association between self-concept clarity and depressive symptoms among college nursing students. A sample of 488 college nursing students participated in this study and completed self-reports of self-concept clarity, emotion regulation, meaning in life, and depressive symptoms. The results showed that self-concept clarity was significantly and negatively associated with depression in nursing students, meaning in life had a partial mediating effect on the relationship between self-concept clarity and depression. Furthermore, emotion regulation ability plays a moderation role of the relationship of self-concept clarity and depression. These findings provide a basis for the relationship between self-concept clarity and depression, and also provide ideas for reducing depression in nursing students.